PENGARUH TINGKAT INVESTASI TERHADAP PERTUMBUHAN EKONOMI DALAM PERSPEKTIF ISLAM - Dinata, Arya Sapta; Rakhman Setyanto, Alief (LP2M Universitas Bina Bangsa, 2025)
This article discusses the influence of investment levels on economic growth from an Islamic perspective. Investment is the main driver of economic growth, but in the context of Islamic economics, deeply held values ​​and principles have a significant impact on investment patterns and their results on economic growth. Through an analysis of literature and Islamic economic concepts, this article describes the relationship between investment levels and economic growth, and examines the factors that influence investment decisions from an Islamic perspective, such as justice, transparency, risk and economic sustainability. In addition, this article highlights the contribution of Islamic economics to inclusive and sustainable economic development. The implications of Islamic economic principles for investment and economic growth, both from an academic and practical perspective, are also discussed. It is hoped that this article will provide valuable insight to further understand how investment can be directed in accordance with Islamic values ​​to achieve sustainable economic development goals